Effective role of Rb doping in controlling the crystallization, crystal imperfections, and microstructural and morphological features of ZnO-NPs synthesized by the sol-gel approach - Sa'aedi, Abdolhossein; Akl, Alaa Ahmed; Hassanien, Ahmed Saeed (CrystEngComm, 2022)
This article is dedicated to synthesizing pure ZnO and Rb-doped ZnO nanoparticles, Rb x Zn 1− x O-NPs ( x = 0.0, 0.02, 0.04, 0.06 mol), using sol-gel technology. Synthesized samples have been characterized and studied using X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), and field-emission scanning electron microscopy (FE-SEM) analysis. The X-ray diffraction study confirmed that Rb x Zn 1− x O NPs have a hexagonal wurtzite polycrystalline structure with the space group C 6 v 4 - P 6 3 mc . XRD studies showed that increasing the Rb concentration leads to a decrease in the observed intensity of diffraction lines; in addition, these lines are slightly shifted towards lower diffraction angles. The texture coefficient (TC) values, degree of crystallinity values, and crystalline and non-crystalline phase percentages of Rb x Zn 1− x O-NPs were also investigated and discussed via analyzing the area under each diffraction peak. The microstructural parameters (crystallite size, D , and average microstrain, 〈 〉) of Rb-ZnO-NPs were also determined using the Scherrer equation, the Williamson-Hall (W-H) method, and size-strain plots (SSPs) via applying the Lorentzian distribution (LD) and Gaussian distribution (GD) to compute the net broadening of diffraction lines. Using the GD and W-H methods, which were the best, it was found that the D -values decreased from 50.67 nm to 34.23 nm, while the 〈 〉-values increased from 1.43 × 10 −3 to 3.48 × 10 −3 when the Rb content increased from zero to 0.06 mol. The EDX findings demonstrated that the compositional element percentages of the Rb x Zn 1− x O-NP samples are in good agreement with those selected. The particle sizes of these NPs range on average from 60 nm to 700 nm and decrease upon increasing the Rb concentration. Generally, the results confirm that the Rb x Zn 1− x O-NPs obtained using the sol-gel technique are regular and uniform in shape and have fine and smooth surfaces. This article is allocated to synthesizing pure ZnO and Rb-doped ZnO nanoparticles, Rb x Zn 1− x O-NPs via the sol-gel technique and then studying the effect of Rb doping ZnO on the crystal structure, microstructure parameters and morphology of the host lattice.